OC-046 5 years on: development of leicester's out of hours bleeder service. (22nd June 2015) - Ramiah, RD; Lim, D; Wurm, P
Abstract : Introduction: University Hospitals of Leicester (UHL) NHS Trust has been offering a comprehensive out of hour (OOH) endoscopy service for almost 10 years. In the wake of rising demands on in-patient endoscopy services we introduced a Consultant led and Gastro-intestinal registrar supported weekday in-reach service in July 2013, with a morning visit to the acute receiving medical units and a daily in-patient emergency list. Our study looked at the effect of this on OOH endoscopy volume, call outs and therapeutic interventions. Method: To compare our data with our previous data set we analysed 6 month periods of OOH data from August to January of each year [2011–15]. Activity was collated by reviewing endoscopy reports [Unisoft reporting tool), separate OOH record books and daily spreadsheet activity returns. We looked at indication and timing of procedures, endoscopic findings, interventions and outcomes. Results: 640 procedures were performed during the study period. The introduction of an in-reach service initially resulted in reduced daytime weekend activity but one-year later weekend activity was back to baseline. Although there was an apparent increase in 'true OOH calls', i.e. 5 pm until 9 am over our 5 year period the absolute numbers remain small and are in fact not different from our previous study, with approximately one emergency procedure per week. There was a 15.9% rise in appropriate referrals as per UHL criteria. Endoscopic findings of varices and variceal bleeding increased by approximately 3.5-fold. There was also a 3.5-fold increase in the proportion of endoscopies employing combination therapy and the use of injection mono-therapy halved, a reflection of recent NICE guidance. 1 The number of patients requiring emergency laparotomy or arterial embolisation remained very small [2–4 cases per 6 month interval]. Conclusion: The total number of procedures has reduced compared to 2006–2010. 2 This is likely to be the result of better education, change in referral pathways and working patterns. The increase of patients presenting with variceal bleeding reflects a nationwide trend. We observed a decrease in the use of adrenaline mon-otherapy and concurrent increase in combination therapy for non-variceal upper gastrointestinal bleeds. Gastroenterology units need to review and re-invent their in-patient and OOH work pattern on a regular basis to address the increasing demands on inpatient endoscopy services. Disclosure of interest: None Declared. References: Acute upper gastrointestinal bleeding:management. NICE Guidance (CG141) June 2012 Ramiah R, Wurm P. Provision of an out-of-hours emergency endoscopy service: the Leicester experience. Frontline Gastroenterol. 2013;4:288–295